CEO’s Emotional Commitment Level and its Firm Capital Structure Choice: Decision Tree Analysis - Ali, AZOUZI Mohamed; Anis, JARBOUI (Asian Journal of Economics and Empirical Research, 2018)
This research examines the determinants of firms’ capital structure introducing a behavioral perspective that has received little attention in corporate finance literature. After discussing the theoretical linking between firm capital structure choice and the CEO’s attitude and behavior, we are showing on empirical grounds the relationship between the manager’s behavior toward the capital structure preferences and his cognitive commitment level. The article explains that the main cause of capital structure choice is CEO commitment level. We introduce an approach based on Decision Tree Analysis technique with a series of semi-directive interviews. The originality of this research is guaranteed since it traits the behavioral corporate policy choice in emergent markets. In the best of knowledge this is the first study in the Tunisian context that explores such area of research. Results show that psychological dimension introduced in the capital structure analysis has enriched the Pecking Order Theory (POT) and the Static Trade Off Theory (STT) CEO (CEO affective commitment) prefer to finance their projects primarily through internal capital, by debt in the second hand and finally by equity.